Monitoring the Effects of Pharmacological Reagents on Mitochondrial Morphology. Issue 1 (24th May 2018) - Fu, Dong; Lippincott‐Schwartz, Jennifer
Abstract: This protocol describes how to apply appropriate pharmacological controls to induce mitochondrial fusion or fission in studies of mitochondria morphology for four different mammalian cell types, HepG2 human liver hepatocellular carcinoma cells, MCF7 human breast adenocarcinoma cells, HEK293 human embryonic kidney cells, and collagen sandwich culture of primary rat hepatocytes. The protocol provides methods of treating cells with these pharmacological controls, staining mitochondria with commercially available MitoTracker Green and TMRE dyes, and imaging the mitochondrial morphology in live cells using a confocal fluorescent microscope. It also describes the cell culture methods needed for this protocol. © 2018 by John Wiley & Sons, Inc.